Quantitative morphological analysis of features of remodeling of the synovial membrane vasculature of the temporomandibular joint in hyperglycemia - Shulgai, A.H.; Hnatiuk , M.S.; Tatarchuk, L.V.; Monastyrska , N.Ya. (Medicni Perspektivi, 2023)
The vasulature of the synovial membrane of the temporomandibular joint of 18 laboratory mature Vietnamese mini male pigs divided into 3 groups was morphologically studied. Group 1 – 6 control experimental animals, 2 – 6 pigs with a 30-day’s experimental hyperglycemia, 3 – 6 pigs with a 60-day’s hyperglycemia. Hyperglycemia was induced by a single intraperitoneal injection of streptozotocin at a dose of 50 mg/kg. Pigs were sacrificed by bloodletting under general thiopental sodium anesthesia 30 and 60 days after the start of the experiment. On the indicated days of the experiment, the concentration of glucose in the blood was determined. On the micropreparations of the synovial membrane of the temporomandibular joint in the small caliber arteries there was measured the diameter of the vessel, the diameter of the lumen, the thickness of the muscular, adventitious membranes, the Wogenworth and Kernogan indices; in the veins – the diameter of the vessel, its lumen, and the thickness of the vein. In arterial and venous vessels, morphometry of endothelial cells, their nuclei, the volume of their damage, and nuclear-cytoplasmic indices were determined. Arterial, metabolic and venous vessels of the hemomicrocirculatory bed were studied morphometrically, their number per 1 mm² of the synovial membrane was determined. Quantitative values were processed statistically. In conditions of experimental hyperglycemia, a thickening of the synovial membrane of the arteries of the temporomandibular joint, a narrowing of their lumen, a decrease in the Kernogan index, an increase in the Wogenvoort index, the volume of damaged endotheliocytes, a disorder of their nuclear-cytoplasmic indices were revealed, an increase in the outer and inner diameters of the veins, the volume of damaged endotheliocytes, disorders of their nuclear-cytoplasmic indexes, plethora was noted. Structural changes in the hemomicrocirculatory bed in experimental hyperglycemia were characterized by a decrease of the diameters of arterioles, precapillary arterioles, hemocapillaries, dilation of capillary venules and venules, marked decrease of microvascular density. The most pronounced degree of remodeling of the studied structures was found in the vessels of the hemomicrocirculatory bed of the synovial membrane of the temporomandibular joint in a 60-day’s experimental hyperglycemia.